2019
DOI: 10.1007/s40995-019-00691-8
|View full text |Cite
|
Sign up to set email alerts
|

Random Laser Emission Spectra of the Normal and Cancerous Thyroid Tissues

Abstract: In this work, the random laser is investigated as a diagnostic method to distinguish between normal and cancerous Rd6Ginfiltrated in vitro human thyroid tissues. The inherent disorder of the tissues provides the necessary condition for the formation of a number of microresonators providing field feedback for lasing. The longer light path random walk inside a scattering media leads to the stronger reabsorption events. Accordingly, a notable redshift of the LIF emission is observed in the random laser spectra of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Several RL spectral properties such as the lasing modes [ 30 ], threshold [ 32 ] and peak shift [ 31 ] were employed to distinguish between healthy and cancerous tissues. Polson et al [ 30 ] reported RLs from R6G-infiltrated human colon tissues.…”
Section: Applications Of Rlsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several RL spectral properties such as the lasing modes [ 30 ], threshold [ 32 ] and peak shift [ 31 ] were employed to distinguish between healthy and cancerous tissues. Polson et al [ 30 ] reported RLs from R6G-infiltrated human colon tissues.…”
Section: Applications Of Rlsmentioning
confidence: 99%
“…This is probably because there are more disorders in malignant grade III tissues. In addition, a wavelength shift can also be applied for cancer diagnosis [ 31 ]. The cancerous thyroid tissues always induce a peak wavelength at the longer-wavelength side compared to the healthy thyroid tissues at the same pumping energy, as shown in Figure 10 c. The author argued that light dwells longer due to more disorders in the cancerous tissues, resulting in a stronger reabsorption and re-emission effect, which causes a stronger peak wavelength redshift.…”
Section: Applications Of Rlsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2004, Polson et al pioneered the demonstration of random lasing emission in biological tissues and, since then, it has been realized in various biological tissues including human organs, such as the brain, breast, thyroid, etc. [3,[7][8][9][10]. Being highly sensitive to disorder, random lasing has been demonstrated to be useful in detecting even nanoscale structural changes and deformations in bones [11].…”
Section: Introductionmentioning
confidence: 99%